2020
DOI: 10.1002/lary.28665
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Lymph Node Status in p16+ Oropharyngeal Cancer After Surgical Treatment

Abstract: Objectives/Hypothesis In this study, we retrospectively reviewed medical records of patients who underwent surgery for p16+ oropharyngeal cancer and analyzed the prognostic implications of pathologic lymph node (LN) status, including number of metastatic LNs, LN ratio, and location of metastatic LNs. Study Design Retrospective case series. Methods We retrospectively reviewed data on patients diagnosed with p16+ oropharyngeal cancer. Results The study population consisted of 159 males and 29 females with a mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…In contrast to our cohort, many recent datasets are skewed towards less locally advanced disease. 30-32 A recent study from the University of Texas MD Anderson Cancer Center described an ORN rate of 13.7% among all HNSCC patients with a 5% rate of grade 4 ORN. A subset analysis generated for the current manuscript demonstrated that 123/826 oropharyngeal cancer patients (14.9%) developed all grade ORN and 42/825 (5.1%) developed grade 4 ORN.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to our cohort, many recent datasets are skewed towards less locally advanced disease. 30-32 A recent study from the University of Texas MD Anderson Cancer Center described an ORN rate of 13.7% among all HNSCC patients with a 5% rate of grade 4 ORN. A subset analysis generated for the current manuscript demonstrated that 123/826 oropharyngeal cancer patients (14.9%) developed all grade ORN and 42/825 (5.1%) developed grade 4 ORN.…”
Section: Discussionmentioning
confidence: 99%